The civil rights movement - Newman, Mark (Historian) (BAAS paperbacks., 2004)
This introduction to the Civil Rights Movement synthesises its history, explaining its origins, development and results as well as historiographical debates. A survey based on a wealth of recent scholarship, it provides a critical perspective on the movement.